An Analysis on How Samsung Can Improve Their Environmental Work by Adding New Ecological Transportation Method of Goods - Wulff, Emma; Kee, Daisy Mui Hung; Halttunen, Ella; Kara, Heidi; Pakarinen, Neea (Asia Pacific Journal of Management and Education (APJME), 2019)
The environment, and in particular the preservation of the earth’s resources, is in no doubt a highly accurate topic. Last years’ reports of future climate disasters have really made people aware of the impact of emissions and consequences of pollutions, which in turn have resulted in protesting and people demanding governments and companies to take their responsible. These events have made companies facing new challenges and are forcing them to work hard on maintaining a strong environmental profile. One huge sector causing emissions is the transport sector, and especially airline transports. Both people and good are transported worldwide every day, causing enormous amounts of emissions. Samsung is one of the worlds’ most influential and powerful brands. Starting as a small business in South Korea in the 1960’s, it has during the past 50 years developed and grown to be a multi-million-industry, offering its products worldwide. One of many reasons behind this success is a strong leadership, combined with following a steady strategy. Being a modern and world-leading company, Samsung also has a clear environmental vision on how the company should work towards a more sustainable society. As this report will show, there is still changes and improvement that can be made, to help Samsung to become even better.